Causes of climate models uncertainty and implications for economic policy - Alfred Greiner (Bielefeld University, Faculty of Business Administration and Economics, 2025)
In this paper it is shown that climate models are characterized by uncertainty and its causes are pointed out. It is well known that a higher greenhouse gas concentration raises the radiative forcing of the earth and the physics behind it is well understood. However, as regards the feedback effects of higher temperatures, parameter uncertainty, model uncertainty and the chaotic nature of the climate system give rise to a considerable degree of ignorance regarding the climate system. Given this uncertainty costly CO2 abatement measures are difficult to justify with the currently available technology. But, due to technical progress more efficient technologies are expected to reduce abatement costs in the future such that a net zero emission policy could be justified to avoid possible, but uncertain, climate damages. In any case, fixing a deadline by which the net zero goal must be met is not welfare maximizing and more flexibility is needed to avoid prohibitive costs.
urn:nbn:de:0070-pub-30015926
Keywords: E61; Q54; 330; Global warming; uncertainty; technology; policy implications